Pengaruh Penggunaan Media Big Book terhadap Kemampuan Membaca dan Menulis Permulaan Siswa Kelas I SDN 35 Pontianak Selatan - Rizal Rizal; Hery Kresnadi; Dyoty Auliya Vilda Ghasya (AS-SABIQUN, 2023)
This study aims to determine the effect of using big book media on the ability to read and write in class I SDN 35 Pontianak Selatan. Specifically, the aims of this study were to find out: (1) Data on the initial reading and writing abilities of students in class I who were not taught using big book media; (2) Data on the initial reading and writing abilities of students in grade I who were taught using the big book media; (3) The effect of using big book media on the ability to read and write beginning in first grade students at SDN 35 Pontianak Selatan. The research method used is the experimental method with the Quasy Experimental form. The sample in this study were 30 students from 87 students selected by purposive sampling technique. The data collection technique for this research is measurement and the data collection tool in this research is a test in the form of a reading and writing test. Data analysis techniques in this study used the average (mean) and t-test. The results of the study can be concluded that: (1) The average reading and writing abilities of students in grade I who are not taught using big book media are 69.20 and 72.96; (2) The average initial reading and writing abilities of students in class I who were not taught using the big book media were 76.53 and 75.6; (3) There is an influence on students' initial reading and writing abilities after being taught using big book media in class I students of SDN 35 Pontianak Selatan.